Femtosecond laser oscillators for high-field science - Südmeyer, T.; Marchese, S. V.; Hashimoto, S.; Baer, C. R. E.; Gingras, G.; Witzel, B.; Keller, U. (Nature photonics, 2008)
Ultrafast laser oscillators have become ubiquitous in science and technology. For many years, however, their pulse energy has been limited to the nanojoule regime. Applications requiring more intense pulses relied on complex amplifier systems, which typically operate at low pulse repetition rates of the order of kilohertz. Recently, the pulse energy of femtosecond laser oscillators has greatly increased, such that some of these experiments can now be driven at multimegahertz repetition rates, which opens promising new avenues for many applications. We review the current state of the art of high-energy femtosecond laser oscillators, in particular mode-locked thin-disk lasers, and discuss their potential to drive high-field science experiments at multimegahertz repetition rates. Diode-pumped thin-disk lasers are now capable of generating femtosecond light pulses with a pulse energy in the microjoule regime at multi-megahertz repetition rates. This review describes the progress that has been made in scaling the performance of such lasers and the applications that may benefit as a result.